Criminal Aspects of Plant Cultivation - Eny Suastuti; Umi Purwandari (Technium Social Sciences Journal, 2023)
Plant cultivation is a very important means of production in realising food self-sufficiency for farmers, considering that cultivating plants is the life and livelihood of farmers. Therefore, it is a wrong action when the government draws up a plan for plant cultivation without involving farmers. The purpose of this research is to examine the extent of the government’s role in strengthening food sovereignty through the implementation of the Plant Cultivation System Law, because the Law does not appear to provide for the rights of farmers. The existence of several cases where farmers are brought to trial for criminal provisions of plant cultivation shows that legal protection has not been carried out on the rights of farmers in maintaining local seeds and conducting plant crosses as charged in court, namely having carried out programs that are contrary to government programs that require the use of certified seeds or seeds produced by seed companies. This research is important to do in order to provide protection to novice farmers in cultivating plants to create a just legal framework. The research method uses normative research with a statutory approach, concept approach and case approach. The results of the study aim to provide a recommendation for strengthening the role of farmer participation in planning their lives and livelihoods so that there is no dependence on seeds originating from companies in accordance with the mandate of Article 28 A of the 1945 Constitution.